Prisão e soltura do ex-presidente lula: a narrativa e a contextualidade a partir das capas de jornais impressos brasileiros - Ranzatti, Mateus Prata (2021)
This research seeks to understand the meaning relationships in the narratives present on the covers of the main newspaper of each region of the country during the release and arrest of former President Luís Inácio Lula da Silva from the contextualities found around the political, economic, cultural and social situation of Brazil during the cases. Through narrative and contextual analyses performed from the reading and understanding of authors such as Laurence Grossberg and Jonathan Culler, this research pursues to recognize which are the meanings that help in identifying the relationship between the two concepts studied. Thus, we have the following guiding question: "What narratives are built by the covers of the newspapers with the highest print circulations across Brazil about the arrest and release of Lula, and how do they connect with the country's political context?”. To this end, we have used covers of five different printed newspapers to be detailed from the narrative presented and have also conducted a contextual media study about the events complementary to the researched facts and that were disseminated by different means of communication. From the analyses and understanding of the selected concepts, we have observed that the narrative meanings found on the covers of the analyzed newspapers are more complex and deep when read from contextual elements in which they are placed.